PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK PADA MATA PELAJARAN PPKN DI KELAS IV SDN CIBOMO - Siti Masfufah; Damanhuri Damanhuri; Ikman Nur Rahman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to develop a comic as a learning media for grade IV students of elementary school. This research was conducted at SDN Cibomo in the academic year of 2020-2021. The type of this research was Research and Development (R&D). The product of this research was a learning media containing the materials about understanding the relationship of symbols with the meaning of moral principles of Pancasila on Civics subject at grade IV of elementary school. The media was a comic printed with the size of A5. Expert validation was used to see the product validity. The validation was carried out by the media experts, material experts, and education experts. The subjects of this research were all grade IV students of SDN Cibomo Serang which were 20 students. Based on the data, the average validation score of the comic media was 94.1% with very feasible category. Then, the average score of students’ response was 94.4% with very feasible. Furthermore, the score from the educators’ responses was 94% which was included in very feasible category. In conclusion, the comic learning media on Civics subject about understanding the relationship of symbols with the meaning of the moral principles of Pancasila was feasible and it could be applied as the teaching materials at grade IV of elementary school.